Effect of different frequency and dose of drip irrigation growing of aloe vera in the Municipality Colina Falcon state - Jorge Raúl Gerardo Nieves; Pedro Pujols Osle; Norge Tornes Torres; Juan Pedro Machado Castillo (Revista Arbitrada Interdisciplinaria Koinonía, 2018)
This research was carried out in the estate "La Estrella" in the Las Ventosas, municipality Colina of the Falcón state, with the objective of evaluating the effect of different frequencies and doses of irrigation by drip irrigation in aloe vera, L. A striped design was used with 4 treatments and 4 contiguous repetitions: T1 without irrigation, T2 irrigation by dripping every 7 days at doses of 0.5 L / plant, T3 irrigation by dripping every 14 days at doses of 1.5 L / Plant, T4 drip irrigation every 21 days at doses of 3 L / plant. The variables length, width, thickness, weight of the penca and weight of the gel were evaluated, as well as the biomass and gel yield. The application of 0.5 liters per plant every 7 days with drip irrigation, allows to obtain greater length, width and thickness of the leaf and high yields in the cultivation of aloe.